Post-infectional biochemical changes in mulberry leaves affected by Cercospora moricola Cook and its effect on cocoon characters of the silkworm, Bombyx mori L. (University Journal of Zoology, Rajshahi University, 2007)
Key words: Mulberry; biochemical changes; cocoon characters; leaf spot disease; Cercospora moricola Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 85-87